ACCOUNTING AND REPORTING OF ESG INDICATORS AS A TOOL FOR ENHANCING BUSINESS TRANSPARENCY IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT - BOHATCHYK, Liudmyla; LOPATOVSKYI, Viktor; LOPATOVSKA, Oksana; MELNYCHUK, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Increasing requirements for business transparency, social responsibility, and environmental safety necessitate the implementation of new approaches to accounting and reporting. Traditional financial statements no longer provide a comprehensive picture of a company’s performance and its impact on society and the environment. Under these conditions, the accounting and reporting of ESG indicators (environmental, social, and governance) become key tools for building trust, strengthening reputational resilience, and achieving the strategic goals of sustainable development. The relevance of the study is driven by the need to develop an effective methodological framework for implementing ESG accounting systems in the corporate practice of Ukrainian enterprises, particularly in the context of their adaptation to European transparency standards and integration into global markets. The aim of this study is to substantiate the theoretical and methodological foundations for forming an ESG accounting and reporting system aimed at enhancing corporate transparency, investor trust, and the implementation of sustainable development principles. The modern paradigm of business development is increasingly guided by the principles of sustainability, responsibility, and openness. Under these conditions, traditional financial reporting can no longer fully reflect a company’s impact on the environment, society, and corporate governance. Therefore, ESG accounting and reporting (Environmental, Social, Governance) are gaining rapid development, forming a comprehensive understanding of the non-financial results of business and complementing the management information system with qualitative indicators of enterprise growth. An important direction of modern corporate governance is the development of an ESG accounting system integrated into a unified information space of the enterprise. This approach enables systematic monitoring of non-financial results, assessment of their impact on business sustainability, and the formation of transparent reporting. ESG accounting serves as a tool for comprehensively reflecting the interconnection between economic performance and social and environmental outcomes, allowing for a more complete understanding of corporate efficiency and strengthening investor confidence. Through effective ESG accounting and systematic reporting, enterprises increase their operational transparency, build trust among investors and society, enhance adaptability to external challenges, and create the foundation for long-term business resilience. An effective methodology for ESG accounting and reporting-based on the combination of international standards, digital technologies, and internal corporate regulations-becomes a key driver in implementing the principles of sustainable development. The results of the study confirm that an effective ESG accounting and reporting system is a key factor in enhancing business transparency, building investor trust, and ensuring sustainable enterprise development. Its formation requires integrating international standards (GRI, SASB, TCFD, ISSB, CSRD) with national regulatory requirements and internal corporate practices. It is established that the development of a modern ESG system should be based on a unified methodological framework for data collection and evaluation, digitalization of accounting processes, use of integrated information platforms, and implementation of external verification of reports as a tool to ensure reliability and trust. Adherence to the principles of materiality, accuracy, completeness, comparability, and transparency determines the quality of corporate reporting and promotes its harmonization with international requirements.